Does the type of funding influence research results – and do researchers influence funders?. (1st June 2020) - Hove, Kjetil Hatlebakk
Abstract : Does a shift from hard to soft funding have an impact on research outcomes? Existing literature suggests that moving from hard money, such as lump-sum government-funded research, to commissioned research entails a greater risk of the researchers being influenced by the principal (the funding body). Based on literature and an empirical study, we identify two types of researcher roles: the influential consultant and the technical realist. The first type studies more advanced, important, and diffuse topics on behalf of principals high up in the hierarchy. They have a much greater experience of the issues discussed in this paper than the technical consultants. During the course of this study, we also discovered that the balance of power is not necessarily as one-sided as theory suggests: researchers can wield significant influence over the principals as well.